2001
DOI: 10.1007/pl00007996
|View full text |Cite
|
Sign up to set email alerts
|

Complex nonlinear dynamics of the Hodgkin–Huxley equations induced by time scale changes

Abstract: The Hodgkin-Huxley equations with a slight modification are investigated, in which the inactivation process (h) of sodium channels or the activation process of potassium channels (n) is slowed down. We show that the equations produce a variety of action potential waveforms ranging from a plateau potential, such as in heart muscle cells, to chaotic bursting firings. When h is slowed down--differently from the case of n variable being slow --chaotic bursting oscillations are observed for a wide range of paramete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 34 publications
4
57
0
Order By: Relevance
“…Bifurcation diagrams can be constructed by the ordinary numerical integration of differential equations if the concepts of bifurcation theory are applied, which is the brute-force method (7,39). However, strict bifurcation (stability) analysis, called the "continuation" method (5,39,47), can determine the stability and bifurcation of EPs (and LCs) more rapidly and accurately even when a system exhibits multistability (coexistence of multiple EPs and LCs) with hysteresis, as suggested for nonlinear systems, including cardiac myocytes (10,21,22).…”
Section: Significance Of Bifurcation Analysismentioning
confidence: 99%
“…Bifurcation diagrams can be constructed by the ordinary numerical integration of differential equations if the concepts of bifurcation theory are applied, which is the brute-force method (7,39). However, strict bifurcation (stability) analysis, called the "continuation" method (5,39,47), can determine the stability and bifurcation of EPs (and LCs) more rapidly and accurately even when a system exhibits multistability (coexistence of multiple EPs and LCs) with hysteresis, as suggested for nonlinear systems, including cardiac myocytes (10,21,22).…”
Section: Significance Of Bifurcation Analysismentioning
confidence: 99%
“…was derived in [6] from a version of the classical HH equations obtained by introducing independent time constants τ m , τ h , τ n in the conductance equations, as suggested in [2,3,4,5]. The value of ǫ that results from this derivation is 1/120 ≈ .0083, which represents the reciprocal of the largest maximal ionic conductance, that of the sodium current, in the original model.…”
Section: Introductionmentioning
confidence: 99%
“…Past work has demonstrated that a step increase in τ h or τ n can lead to the existence of mixed-mode oscillations (MMOs), featuring alternating sets of large excursions and of small (or subthreshold) oscillations (STOs) in v, as solutions of the dimensional form of (1.1) [2,3,4,5]; see Figure 2. In [6], we used recently developed mathematical theory [8,10,11] to explain the onset and offset of MMOs in system (1.4) under the systematic, independent variation of τ h , τ n , and I.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Hodgkin-Huxley model was described in 1952 [93], the chaotic property of spontaneous high-frequency action potential in excitable cells had been regarded as a vital characteristic of fibrillation action potential and kept on being studied in non-linear system by the intensive research [94,95,[97][98][99], the chaotic property exhibited system instability with the unstable action potential amplitude and duration. The Hodgkin-Huxley model per se is a set of nonlinear ordinary differential equations that approximate the electrical characteristics of excitable cells such as neurons and cardiac myocytes (non-linear system refers to the system whose variations of results are non-consistent).…”
Section: Butterfly Effect and Chaotic Propertymentioning
confidence: 99%